Optimizing Bone Mass and Strength: The role of physical activity and nutrition during growth (Medicine and Sport Science, 2007)
The recognition that osteoporosis is a major public health problem that is projected to escalate as our population ages has led to an ever-increasing amount of research into strategies to prevent and manage this disease. Although traditionally considered to be a disease affecting the elderly, increased recognition that osteoporosis may have its foundation early in life has stimulated substantial research interest into factors which can influence skeletal development, including both genetic and lifestyle factors. Recent advancements in bone imaging technology have also led to a rapid expansion in our understanding of the structural and biomechanical basis for changes in bone strength during both normal growth and in response to lifestyle factors such as physical activity and nutrition. With the emergence of this new information, the need for a clear, concise and comprehensive state-of-the-art account of the latest developments in this field is critically important so that health professionals, scientists and graduate students are informed of recent evidence-based knowledge on how to optimize skeletal development. The purpose of this book is to provide a critical analysis and summary of the current state of knowledge of factors that influence the development of bone health during childhood and adolescence. The chapter by Faulkner and Bailey highlights the importance of the first two decades of life to optimize peak bone mass, with an emphasis on the rationale for adopting public health approaches to prevent this disease. The chapter by Kontulainen et al. provides new insights into the structural and biomechanical basis for changes in bone strength during growth, including a brief review of the key hormonal factors which regulate skeletal development. The chapters by Daly and by Specker and Vukovich extend this theme by examining the effects of physical activity and nutrition alone and in combination on the mass, geometry and strength of growing bone. This is followed, in the chapter by Bonjour et al., by an overview of the genetic influence on peak bone mass, and recent developments in gene-environmental interactions with regard to the skeletal responses to exercise and nutrition. The chapter by Zanker and Hind focuses on the effect of menstrual cycle disturbances and disordered eating on skeletal health in young athletes and includes recommendations for the prevention and treatment of low bone density in female athletes. The chapter by Goulding provides a thorough review of the key determinants of childhood fractures, which is followed by a concise summary by Karlsson of the latest evidence on whether exercise-induced skeletal benefits sustained during growth are maintained into old age when most fractures occur. The final chapter by Hughes et al. provides practical, real-world guidance on lifestyle strategies and guidelines, including sample programs that can be adopted by health care professionals to optimize bone health during growth. The information in this book will benefit a range of health care professionals and scientists, including exercise specialists, pediatricians, nutritionists and dietitians, biomedical researchers and graduate students, health promotion workers and public health professionals. Specifically, for those health professionals who want a comprehensive review and critical analysis of both the existing and current literature, this book provides an excellent source of information. Public health professionals will also find this book a thought-provoking reference as it will help them understand the theoretical basis for practical exercise and nutrition guidelines to optimize bone health during growth. There is also practical information for physical educators and others wishing to add 'bone-healthy' activities to their curriculum.